DISTORTION OF CAPACITY ON INTER-REGIONAL TRADE OF IMT-GT: STUDY CASES ON FOUR SELECTED PROVINCES IN SUMATRA, INDONESIA) - Avianto, Benito Rio (Journal of Indonesian Economy and Business, 2010)
The objective of the paper was to understand the impact of sub regional economic cooperation, known as the Indonesia-Malaysia-Thailand Growth Triangle (IMT- GT), ontrade sector in Indonesia. The approach of research based on export macro information by provinces and commodities.The method used in the analytical framework was a fixed effect method. The regional study covered Nanggroe Aceh Darussalam, North Sumatera, West Sumatera Barat, andRiau provinces, and the commodities involved CPO, coffee and rubber, with 1990-2008 data series.Based on pooled regression, the IMT-GT, there was a significant impact on export from the four provinces to Malaysia and Thailand for all based years. One might focus on commodity level that, in fact, CPO was the only one coomodity that had a significant impact within the IMT GT region. In addition, Thai Bath and Malaysian Ringgit, withrespect to GDP for both countries, had significant influenced on Export;, especially after the IMT GT endorsed.Keywords: IMT-GT, Province, export, CPO, coffee, and rubber export, pooled regression